2020
DOI: 10.1038/s41598-020-76692-0
|View full text |Cite
|
Sign up to set email alerts
|

Recycling biofloc waste as novel protein source for crayfish with special reference to crayfish nutritional standards and growth trajectory

Abstract: Screening of novel feedstuffs, that too for data-deficient (nutritionally) animals, is somewhat ambiguous or problematic. Through systematic meta-analyses, the present study formulated most up-to-date crayfish nutritional standards, against which a recyclable waste (biofloc biomass, BM) from intensive aquaculture systems was assessed as a novel protein source. Growth trajectory dependencies and thermal growth coefficient qualifying for good growth in crayfish (TGC 0.5–0.64 units) were benchmarked. Using these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Among native rheophilic cyprinids considered, species with statistically similar ( p > 0.05) body composition were assumed and classified to be similar in terms of nutritional requirements. The tests were performed using RStudio v1.2.5042 using libraries ‘e1071’, ‘dunn.test’ and ‘FSA’ [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among native rheophilic cyprinids considered, species with statistically similar ( p > 0.05) body composition were assumed and classified to be similar in terms of nutritional requirements. The tests were performed using RStudio v1.2.5042 using libraries ‘e1071’, ‘dunn.test’ and ‘FSA’ [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were achieved in the dietary inclusion of 15.6% biofloc meal and the 7.8% biofloc meal with FO inclusion experiments, indicating that this approach was reproducible (Kuhn et al., 2009). An additional study carried out on red swamp crayfish ( Procambarus clarkii ) suggested that biofloc meal supplied alongside existing feed at a rate of 33%–66% inclusion can elevate growth rate; however, beyond 66% inclusion reduces growth rate owing to the increased ash content which eventually exceeds the species limit at 14% (Lunda et al., 2020).…”
Section: Importance Of Microorganisms and Zooplankton In Bftmentioning
confidence: 99%
“…An additional study carried out on red swamp crayfish (Procambarus clarkii) suggested that biofloc meal supplied alongside existing feed at a rate of 33%-66% inclusion can elevate growth rate; however, beyond 66% inclusion reduces growth rate owing to the increased ash content which eventually exceeds the species limit at 14% (Lunda et al, 2020).…”
Section: Biofloc Mealmentioning
confidence: 99%
“…In contrast, the Arthropoda phyla (subphylum crustacea and class insecta) possess limited regenerative ability, although they provide insights into conserved regenerative mechanisms and systems 5,6 . Freshwater crayfish (Crustacea, Decapoda, Astacida) are a diverse taxonomic group, endemic to the continents of North America, Australia‐Oceania and Europe 7 . They can regenerate various anatomical structures, such as chelipeds, pereiopods, uropods, antennae, brain neurons and the compound eye 8,9 .…”
Section: Introductionmentioning
confidence: 99%